Preparation method and application of L-type low-temperature shift catalyst

By using a twin-screw reactive extruder in an aluminum sol system, the full mixing and dispersion of Cu, Zn and zirconium precursors, combined with flash drying and forming processes, the existing low-temperature transformation catalyst preparation process is solved, and other problems such as long and high cost are solved. , a catalyst with high conversion rate, heat resistance and long service life was prepared.

CN119500148AActive Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311046151.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-25
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

The existing low-temperature transformation catalyst preparation process is long, the cost is high, the specific gravity of the stack is high, the catalyst loading volume is large, the active copper microcrystals are large, and they are easy to fusion and grow under high loads, and the service time is short.

Method used

In the aluminum sol system, the precursor of Cu, Zn and zirconium and the additive inorganic salt are added, and the mixture is thoroughly mixed, sheared and dispersed by a twin-screw reactive extruder to form a slurry, followed by a molding lubricant and flashing The dryer is dried and finally passed through pre-filtering and crushing to obtain a finished catalyst without calcination.

Benefits of technology

The prepared L-type low-temperature transformation catalyst has low specific gravity, large specific surface area, small copper grain size, high conversion rate, good heat resistance, extended service life from 3 years to more than 4 years, and low methanol content of by-products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method and application of an L-type low-temperature shift catalyst. The preparation method comprises the following steps: adding active substances such as a precursor of Cu, a precursor of Zn and a precursor of zirconium and auxiliaries such as inorganic salt into an aluminum sol system, and fully mixing, shearing and dispersing through a double-screw reactive extruder to form slurry; adding a forming lubricant into the mixed material, drying at 300-350 DEG C, and directly pre-tabletting the material subjected to intermediate phase decomposition; and crushing, tabletting and forming to obtain a finished product catalyst without calcination. According to the catalyst, the dispersity of active copper microcrystals on a carrier is improved, crystal grains are not easy to grow up under a high-temperature condition, the thermal stability of the catalyst during use is kept, and the heat-resistant temperature is improved by 10 DEG C or above compared with a common shift catalyst; due to the addition of the auxiliary agent, the content of byproduct methanol after the shift reaction is lower than 300ppm. The bulk specific gravity of the catalyst is smaller than 1.25 g / cm < 3 >, and the specific surface area is larger than 100 cm < 2 > / The catalyst is mainly applied to deep conversion with the low-change CO content of 2-7%, the conversion rate is higher than 95%, and the outlet CO content is lower than 0.2%. After 4 hours of heat resistance at 400 DEG C, the conversion rate of active CO is greater than 80%, and the copper grain size is less than 8 nm, so that the service life of the catalyst is prolonged from 3 years to 4 years or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of an L-type low-temperature shift catalyst, which is particularly suitable for low-temperature shift of ammonia synthesis process, deep conversion of low-CO content of 2-7%, and can also be used for methanol synthesis of co-alcohol. The process flow is short, stable and reliable, no calcination is required, and the cost is low. The catalyst pile prepared by the special process has low specific gravity, small copper crystal size, large specific surface area, high conversion rate, and can still maintain high activity after heat resistance, so that the service life of the catalyst is extended from 3 years to more than 4 years. Background Art

[0002] At present, the preparation method of low-temperature shift catalyst is mainly co-precipitation. The nitrates of copper and zinc react with the precipitant to form a binary slurry after co-precipitation, which is then loaded onto the carrier aluminum gel and goes through the processes of washing, filtering, drying, granulation, calcination and tableting. The production cycle is long and the equipment investment cost is high. In addition, the prepared catalyst has problems such as high bulk density, large original particle size of active copper microcrystals, small specific surface area, poor heat resistance and short life. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation method and application of an L-type low-temperature shift catalyst, so as to solve the problems of long preparation process, high cost, high bulk density, large catalyst loading, large original particle size of active copper microcrystals, easy fusion and growth under high load, and short service life of the current low-temperature shift copper-based catalyst.

[0004] The present invention discloses a preparation method and application of an L-type low-temperature shift catalyst. The main steps are to add the precursor of active material Cu, precursor of Zn and precursor of zirconium and auxiliary inorganic salt etc. into an aluminum sol system at 80°C; fully mix, shear and disperse through a twin-screw reactive extruder to form a slurry; add a molding lubricant to the mixed material, enter a flash dryer through a metering pump to exchange heat with hot air, and the dried and decomposed material is pre-compressed and crushed and then molded to obtain a finished catalyst that does not require calcination.

[0005] The main technical scheme of the present invention: a preparation method of an L-type low-temperature conversion catalyst, characterized in that a catalyst formula containing copper, zinc and zirconium substances is used, and in an aluminum sol system, a precursor of active material Cu, a precursor of Zn and a precursor of zirconium and an auxiliary inorganic salt are added at 70-80°C; a twin-screw reactive extruder is used to fully mix, shear and disperse to form a slurry; the mixed material is added with a molding lubricant for drying, and enters a flash dryer for heat exchange with hot air. The dried and decomposed material is pre-compressed and crushed and then molded to obtain a finished catalyst that does not require calcination.

[0006] Furthermore, Al in aluminum sol 3+The concentration is not more than 50 g / L, and the preferred concentration is 5, 15, 25, or 35 g / L; the inorganic aluminum salt of the aluminum sol is preferably Al(NO3)3·9H2O.

[0007] The aluminum sol is prepared by a powder dispersion method, an inorganic salt raw material method, an organic salt hydrolysis method or an aluminum-hydrochloric acid method, and the inorganic salt raw material method is preferred.

[0008] The Cu precursor is sourced from Cu inorganic salts, composite salts and complex copper or a mixture of several thereof.

[0009] Preferably, the source of Cu is Cu(OH)2 solution, and the concentration is controlled at 20-40 g / L.

[0010] The Zn precursor is a source of Zn, which is an inorganic salt, a composite salt and a mixture of complex zinc or several thereof.

[0011] Preferably, the source of Zn is Zn2(OH)2CO3 solution, and the concentration is controlled at 20-40 g / L.

[0012] The zirconium precursor is derived from Zr nitrate, preferably Zr(NO3)4·5H2O, and the concentration is controlled at 5-25 g / L.

[0013] The auxiliary inorganic salt is carbonate or nitrate, preferably KHCO3, and the concentration is controlled at 2-8 g / L.

[0014] In the preparation method of the present invention, the front end of the twin-screw reactive extruder is provided with multiple feeding ports for inorganic aluminum salts, precipitants, and nitric acid; the middle end is provided with multiple feeding ports for Cu precursors, Zn precursors, zirconium precursors and auxiliary inorganic salts; the end is provided with an exhaust port; a weir flow plate of a certain height is provided in front of the middle end to enhance material mixing; the twin-screw reactive extruder adopts an electric heating module as a whole, and is heated in sections and stages, with a temperature adjustment range of 20-500°C; preferably, the twin-screw reactive extruder is provided with automatic weighing, automatic metering, and automatic continuity facilities.

[0015] The molding lubricant is any one of alcohol, ester and graphite, preferably graphite, and the added amount is not more than 10wt%.

[0016] The material is dried and calcined instantly after heat exchange with 300°C-350°C hot air in a flash dryer, and the discharged material is in powder form.

[0017] The material pressed out of the pre-compression tablet is a strip-shaped structure or a circular structure, preferably a strip-shaped structure, with a size of 2.0-5.0 mm*2.0-5.0 mm*0.5-2 mm.

[0018] The L-type low-temperature shift catalyst prepared by the method of the present invention is mainly used for low-temperature shift of ammonia synthesis process, deep conversion of low-CO content of 2-7%, or for methanol synthesis of combined alcohol.

[0019] The "L" in the L-type low-temperature shift catalyst of the present invention represents low bulk density; for details, see the enterprise standard Q / SH 1170083-2022 "B207-L-type carbon monoxide low-temperature shift catalyst".

[0020] The L-type low-temperature shift catalyst provided by the present invention improves the dispersion of active copper microcrystals on the carrier, and the crystals are not easy to grow under high temperature conditions, maintaining the thermal stability of the catalyst during use, and the heat resistance temperature is increased by more than 10°C compared with ordinary shift catalysts; due to the addition of additives, the content of byproduct methanol after the shift reaction is less than 300ppm. The specific gravity of the catalyst pile is less than 1.25g / cm 3 , with a surface area greater than 100cm 2 / g. It is mainly used for deep conversion of low-variable CO content 2-7%, with a conversion rate higher than 95% and an outlet CO content lower than 0.2%. The active CO conversion rate after 4h of heat resistance at 400℃ is higher than 80%, and the copper grain size is less than 8nm, which extends the service life of the catalyst from 3 years to more than 4 years. Implementation

[0021] The present invention is described in detail below through examples. The following examples are only for further explaining the content of the present invention and illustrating the effects of the present invention, and the effects of the method of the present invention are not limited thereto. Example

[0022] In the embodiment, aluminum sol is prepared at the front end of a twin-screw reactive extruder, Al(NO3)3·9H2O and precipitant NaOH are added to parallel feeding ports A and B at the front end, respectively, and a feeding port C is provided at the check section for adding acid to adjust the pH to control the pH of the aluminum sol between 6.8 and 7.2; active substances Cu, Zn, zirconium precursors and auxiliary inorganic salts are added to four groups of parallel feeding ports D, E, F and G at the middle end, respectively.

[0023] In the embodiment, a twin-screw extrusion process is used to replace the traditional mechanical stirring to achieve continuous production of the catalyst, and the shearing, mixing and dispersing effects of the twin-screw and weir plate are utilized to enhance the mixing effect between the materials.

[0024] In the embodiment, after the molding lubricant is added to the slurry, it enters the flash dryer through a metering pump, and exchanges heat with 300°C-350°C hot air in the dryer. During the drying process, the material after the intermediate phase decomposition can be directly pre-compressed into tablets. The pre-compressed tablets are strip-shaped structures with dimensions of 2.0~5.0mm in length, 2.0~5.0mm in width, and 0.5~2mm in thickness. The pre-compressed tablets are crushed, sieved through 100 mesh, and formed into tablets to obtain finished catalysts that do not require calcination. Example 1

[0025] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum sol with a concentration of 5g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 5g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of molding lubricant graphite is added, and the finished catalyst CAT-1 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 2

[0026] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 15g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 5g / L auxiliary agent KHCO3 are respectively added to four groups of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst product CAT-2 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 3

[0027] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 5g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-3 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 4

[0028] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 35g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 5g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-4 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 5

[0029] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 2g / L auxiliary agent KHCO3 are respectively added to four groups of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-5 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 6

[0030] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-6 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 7

[0031] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 25g / L; 30g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-7 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 8

[0032] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 25g / L; 20g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four groups of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-8 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 9

[0033] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 30g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four groups of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-9 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 10

[0034] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 20g / L Zn2(OH)2CO3, 15g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four groups of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst product CAT-10 is obtained through flash evaporation, pre-tabletting, crushing and molding. Embodiment 11

[0035] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al 3+ Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 10g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added to four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-11 is obtained through flash evaporation, pre-tabletting, crushing and molding. Example 12

[0036] Al(NO3)3·9H2O and 1 mol / L precipitant NaOH solution were added to the parallel feed ports A and B at the front end of the twin-screw reactive extruder respectively, and the shearing and mixing effects of the twin screws and weir plates were used to achieve full mixing. Acid was added to the subsequent feed port C to adjust the pH of the aluminum sol to 6.8-7.2, and the temperature was controlled at 75-78°C to obtain Al3+ Aluminum gel with a concentration of 25g / L; 40g / L Cu(OH)2, 40g / L Zn2(OH)2CO3, 5g / L Zr(NO3)4·5H2O and 8g / L auxiliary agent KHCO3 are respectively added into four sets of parallel feeding ports D, E, F and G at the middle end of the extruder to make slurry, and then 0.5-2wt% of lubricant graphite is added, and the finished catalyst CAT-12 is obtained through flash evaporation, pre-tabletting, crushing and molding.

[0037] Comparison sample A commercially available B207 low temperature shift catalyst was used as a comparison sample and named CAT-Sample.

[0038] Sample testing Catalyst sample: particle size 0.425~1.180 mm.

[0039] Heat resistance pre-activity test: The activity test conditions are as follows: a double-tube (or single-tube) reactor with an inner diameter of 24 mm; catalyst loading: 30 mL; activity test pressure: 2.0 MPa ± 0.02 MPa; activity test space velocity: 4000 h -1 ±50h -1 ; Activity measurement temperature: 200℃±1℃; Volume ratio of water vapor to raw gas: 0.33±0.02; Raw gas composition (by volume fraction): carbon monoxide (2.5%~4.0%), carbon dioxide (14.0%~20.0%), and the rest is hydrogen and nitrogen (3:1).

[0040] Activity test after heat resistance: The reactor pressure was increased to 2.0 MPa within 0.5 h, and the air velocity was increased to 4000 h -1 ; Raise the reactor temperature to 400℃ within 1 hour, maintain for 4 hours, and then quickly cool it down to 200℃; raise the temperature of the insulation tube vaporizer at the same time, control the insulation tube temperature to about 150℃ and the vaporizer temperature to about 250℃; start the horizontal flow pump, and after the reactor pressure, temperature, feed gas space velocity, water vapor ratio and vaporizer temperature are stable for 2h to 3h, use a gas chromatograph (or other carbon monoxide analyzer) to analyze the carbon monoxide volume fraction in the feed gas and the conversion gas, and calculate its carbon monoxide conversion rate, and then analyze it every 1h to 1.5h. When the absolute difference of the carbon monoxide conversion rate measured three times in a row is less than or equal to 2%, the test can be ended.

[0041] The activity test results are shown in Table 1. Catalyst samples CAT-1, CAT-2, CAT-3, CAT-4, CAT-5, CAT-6, CAT-7, CAT-8, CAT-9, CAT-10, CAT-11 and CAT-12 are prepared by the present invention.

[0042] Table 1 Activity test results .

[0043] The catalysts were evaluated for their heat resistance and the results are shown in Table 2.

[0044] Table 2 Bulk density measurement results .

[0045] It can be seen from Tables 1 and 2 that the specific gravity of the low-temperature shift catalyst prepared by the present invention is less than 1.25 g / cm 3 The specific surface area is higher than that of the control catalyst, the copper crystal size is less than 8nm, the active substance is more evenly dispersed, the by-product methanol content is less than 300ppm, the selectivity is higher, the CO conversion rate is higher than 95%, and after 4h of heat resistance at 400℃, the activity is still greater than 80%, indicating that the present invention has obvious advantages over the existing catalyst production methods and has broad market prospects.

Claims

1. A method for preparing an L-type low-temperature shift catalyst, characterized in that A catalyst formula containing copper, zinc and zirconium substances is adopted. In the aluminum sol system, the precursors of active substances Cu, Zn and zirconium and the inorganic salt additive are added at 70-80°C. The mixture is fully mixed, sheared and dispersed through a twin-screw reactive extruder to form a slurry. The mixed materials are added with a molding lubricant for drying and enter a flash dryer for heat exchange with hot air. The dried and decomposed materials are pre-compressed and crushed and then molded to obtain a finished catalyst that does not require calcination.

2. The preparation method according to claim 1, characterized in that Al in aluminum sol 3+ The concentration is not more than 50 g / L, and the preferred concentration is 5, 15, 25, or 35 g / L; the inorganic aluminum salt of the aluminum sol is preferably Al(NO3)3·9H2O.

3. The preparation method according to claims 1 and 2, characterized in that Aluminum sol can be prepared by a powder dispersion method, an inorganic salt raw material method, an organic salt hydrolysis method or an aluminum-hydrochloric acid method, and the inorganic salt raw material method is preferred.

4. The preparation method according to claim 1, characterized in that The precursor of Cu, the source of Cu is one or a mixture of Cu inorganic salt, composite salt and complex copper.

5. The preparation method according to claim 4, characterized in that The source of Cu is Cu(OH)2 solution, and the concentration is controlled at 20-40g / L.

6. The preparation method according to claim 1, characterized in that The precursor of Zn, the source of Zn is one or a mixture of inorganic salts, composite salts and complex zinc of Zn.

7. The preparation method according to claim 6, characterized in that The source of Zn is Zn2(OH)2CO3 solution, and the concentration is controlled at 20-40g / L.

8. The preparation method according to claim 1, characterized in that The precursor of zirconium, the source of zirconium is Zr nitrate, preferably Zr(NO3)4·5H2O, and the concentration is controlled at 5-25g / L.

9. The preparation method according to claim 1, characterized in that The inorganic salt additive is carbonate or nitrate, preferably KHCO 3, The concentration is controlled at 2-8g / L.

10. The preparation method according to claim 1, characterized in that The front end of the twin-screw reactive extruder is provided with multiple feeding ports for inorganic aluminum salts, precipitants, and nitric acid; the middle end is provided with multiple feeding ports for Cu precursors, Zn precursors, zirconium precursors and auxiliary inorganic salts; the end is provided with an exhaust port; a weir flow plate of a certain height is provided in front of the middle end to enhance material mixing; the twin-screw reactive extruder adopts an electric heating module as a whole, with divided and segmented heating, and the temperature adjustment range is 20-500°C; preferably, the twin-screw reactive extruder is provided with automatic weighing, automatic metering, and automatic continuity facilities.

11. The preparation method according to claim 1, characterized in that The molding lubricant is any one of alcohol, ester and graphite, preferably graphite, and the added amount is not more than 10wt%.

12. The preparation method according to claim 1, characterized in that After the material is exchanged with 300℃-350℃ hot air in the flash dryer, it is instantly dried and calcined, and the output state is powder.

13. The preparation method according to claim 1, characterized in that The material pressed out of the pre-compression tablet is a strip structure or a circular structure, preferably a strip structure, with dimensions of 2.0-5.0 mm in length, 2.0-5.0 mm in width, and 0.5-2 mm in thickness.

14. An application of an L-type low-temperature shift catalyst prepared by any of the methods of claims 1 to 13, characterized in that It is used for low temperature conversion of ammonia synthesis process, deep conversion of low CO content 2~7%, or for methanol synthesis of co-alcohol.

Citation Information

Patent Citations

  • Preparation method of copper, zinc, aluminum and zirconium catalyst

    CN107115865A

  • Preparation method of low temperature shift catalyst with low bulk specific gravity and high activity

    CN107115866A

  • Low-temperature water vapor shift reaction and catalyst thereof

    CN113135551A

  • Catalysts containing copper, zinc oxide, alumina and silica

    CN113557087A

  • Method for manufacturing catalyst for removing carbon monoxide

    JP2008104906A